Best Uniform Approximation of a Family of Functions Continuous on a Compact Set - Hnatyuk, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate the problem of the best uniform approximation of a function continuous on a compact set. We generalize the principal results of this investigation to the problem of the best simultaneous uniform approximation of a family of functions continuous on a compact set.